Analisis Konsep Dan Struktur Kurikulum Merdeka Dan Merdeka Belajar - Ummi Salamah; Yuni Listiyani; Mustafiyanti Mustafiyanti (Pusat Riset dan Inovasi Nasional, 2024)
The Indonesian government has launched the concept of “Merdeka Belajar” as an effort to improve the quality of education in Indonesia. This concept aims to provide greater freedom and autonomy to educational units in managing and developing their curriculum according to the needs and potential of students. In this paper, we analyze the concept and structure of Merdeka Belajar curriculum which includes four main components, namely: (1) Merdeka Belajar Policy; (2) Merdeka Belajar Curriculum; (3) Merdeka Belajar Learning; and (4) Merdeka Belajar Assessment. Merdeka Belajar Policy gives greater authority to schools in developing curriculum and learning plans according to local needs. Merdeka Belajar Curriculum focuses on developing core competencies and basic competencies needed by students to face the challenges of the 21st century. Merdeka Belajar Learning encourages teachers to use innovative learning methods, such as project-based learning, problem-based learning, and collaborative learning. Merdeka Belajar assessment emphasizes authentic assessment that measures the ability of students holistically. The application of Merdeka Belajar concept is expected to produce graduates who have competencies that are in line with the needs of industry and society, and are able to think critically, creatively, and innovatively.